Naturalización de ciudadanos en Teos (SEG XXXI 985) (Minerva, 2019)
So me variants are suggested for the reading and interpretation of an inscription found in 1976 in a Turkish village near the old place of Teos. They provide an improved intelligibility of the historical context of this document: in this very moment Teos is extending the access to citizenship, possibly to favour reconstruction after the city was destroyed by the Persians, and also trying to secure the ongoing social and political stability.The policies of the Greek colony of Emporion towards the neighbouring indigenous populations, according notices by Strabo and the evidences of recent epigraphic and archaeological findings, are shown to be strongly parallel to those of Teos by this updated reading of the analysed Teos document.